Dynamic Kerr and Pockels electro-optics of liquid crystals in nanopores for active photonic metamaterials. Issue 44 (5th November 2021) - Kityk, Andriy V.; Nowak, Marcjan; Reben, Manuela; Pawlik, Piotr; Lelonek, Monika; Andrushchak, Anatoliy; Shchur, Yaroslav; Andrushchak, Nazariy; Huber, Patrick
Abstract : A liquid crystal-infused nanoporous solid acts as a photonic metamaterial with thermo-electrically tunable static and dynamic birefringence. Abstract : Photonic metamaterials with properties unattainable in base materials are already beginning to revolutionize optical component design. However, their exceptional characteristics are often static, as artificially engineered into the material during the fabrication process. This limits their application for in-operando adjustable optical devices and active optics in general. Here, for a hybrid material consisting of a liquid crystal-infused nanoporous solid, we demonstrate active and dynamic control of its meta-optics by applying alternating electric fields parallel to the long axes of its cylindrical pores. First-harmonic Pockels and second-harmonic Kerr birefringence responses, strongly depending on the excitation frequency and temperature, are observed in a frequency range from 50 Hz to 50 kHz. This peculiar behavior is quantitatively traced by a Landau–De Gennes free energy analysis to an order–disorder orientational transition of the rod-like mesogens and intimately related changes in the molecular mobilities and polar anchoring at the solid walls on the single-pore, meta-atomic scale. Thus, our study provides evidence that liquid crystal-infused nanopores exhibit integrated multi-physical couplings and reversible phase changes that make them particularly promising for the design of photonic metamaterials with thermo-electrically tunable birefringence in the emerging field of space–time metamaterials aiming at full spatio-temporal control of light.